Response of Trigonella foenum-graecum to organic manures and Rhizobium inoculation in a Typic Haplustept - G Lal, K Kant, Y K Sharma, S F Ali, Naimuddin Naimuddin, O P Aishwath, (Journal of Spices and Aromatic Crops, 2014)
Field experiments carried out to study the effect of organic manures and Rhizobium on performance of fenugreek (Trigonella foenum-graecum) revealed that germination was hastened by the application of organic manures [Vermicompost (VC), Sheep manure (SM) and Farmyard manure (FYM)] and seed inoculation with Rhizobium. Plant height and number of branches were higher with FYM. However, there was no significant variation in days to flower initiation and complete flowering. Yield and yield attributes i.e. number of pods plant-1, number of seeds pod-1 and seed test weight were maximum with FYM. Application of manures and Rhizobium inoculation enhanced the seed yield. Per cent seed yield increase with Rhizobium inoculation, sheep manure, vermi-compost and FYM was 11.45, 22.91, 20.83 and 35.41, respectively. Harvest Index and protein content were highest with FYM.